Analisis Nilai Sosial pada Konten #Nasihatayah Di akun Instagram @ahmadrisyad - Andi Nursyaeba; Kamaluddin Tajibu; M. Anshar Akil; Najamuddin (Danudirja Setyabudi Nusantara, 2026)
The objectives of this study are to identify and examine the social values in the #Nasihatayah content on the Instagram account @ahmadrisyad, to identify the role of the Instagram account @ahmadrisyad in promoting positive values through #Nasihatayah content, and to analyze audience responses to #Nasihatayah content on the Instagram account @ahmadrisyad. This is a qualitative study that uses Philipp Mayring’s qualitative content analysis model, employing data reduction, categorization, coding, and narrative construction from emerging patterns. The data examined by the author consisted of Instagram Reels from the @ahmadriyad account that used the #Nasihatayah hashtag, uploaded from January through March 2025, totaling 76 Reels. The results indicate that the predominance of spiritual values particularly moral and religious values suggests that the da’wah messages in the #Nasihatayah content are oriented toward fostering moral character, spiritual awareness, and the character development of the audience. Material and vital values serve as supporting values for meeting basic needs, maintaining social order, and the wise use of resources and the environment. Meanwhile, the values of truth and beauty strengthen the audience’s rational and emotional well-being by encouraging objective, reflective thinking and maintaining inner harmony and a simple lifestyle. Additionally, the Instagram account @ahmadrisyad plays a significant role in promoting positive social values in the digital space. This account serves as a platform for digital da’wah, an educational medium, a tool for encouraging positive behavior, a source of inspiration, a community builder, and a means of social control. The #Nasihatayah content receives strong positive engagement, as evidenced by high engagement rates and a predominance of appreciative, reflective, and emotional comments.